Phenotype and genotypes Malay traditional house in West Kalimantan (ARTEKS : Jurnal Teknik Arsitektur, 2020)
At the beginning of the 20th century, the terms genotype and phenotype in biology were adopted into architecture. In the science of architecture genotype was an abstract relational model that governs the arrangement of space, and the principle of organizing space while phenotype was a physical form of architecture. Genotype passed from generation to generation thus informing an identity in the community. The development of globalization and the environment can influence the identity of architectural diversity in each region. Vulnerability in the transformation of architectural forms can have an impact on identities that can survive or disappear. Malay traditional houses in West Kalimantan are on stilts and are located on the riverside. the sample used is a traditional Malay house around the palace in West Kalimantan with a sample of 8 cities and uses 69 sample houses. The method in this study uses the Levi Strauss structuralism and configuration space. External structure analysis has an informed of variation phenotype. through configuration space to finding archetypes. Then, continue to inner structure analysis to finding genotype from that archetype. The result from this study found the value and meanings of principle and arrangement space in traditional Malay house in West Kalimantan in the form of zoning of men and women as well as clean and dirty zones which have always been passed down from generation to generation.
Keywords: phenotype; genotype; traditional architecture; houses